Facile synthesis and characterization of conducting polymer-metal oxide based core-shell PANI-Pr2O–NiO–Co3O4 nanocomposite: As electrode material for supercapacitor. Issue 13 (1st July 2021) - Naveed ur Rehman, Muhammad; Munawar, Tauseef; Nadeem, Muhammad Shahid; Mukhtar, Faisal; Maqbool, Adnan; Riaz, Muhammad; Manzoor, Sumaira; Ashiq, Muhammad Naeem; Iqbal, Faisal
Abstract: Metal oxide nanoparticles and their composites with conducting polymers, specifically Polyaniline (PANI) were utilized for fabricating nanoscale supercapacitor (SC) electrode materials. In the present study, we have synthesized pristine Pr2 O3, NiO, Co3 O4 nanoparticles, binary PANI-Pr2 O3, PANI-NiO, PANI-Co3 O4, ternary Pr2 O3 –NiO–Co3 O4, and quaternary PANI-Pr2 O3 –NiO–Co3 O4 spherical core-shell nanocomposite using co-precipitation and ultra-sonication methods. The grown samples were characterized with different analytical techniques. The XRD pattern revealed that the as-synthesized products were crystalline with Pr2 O3 hexagonal phase, NiO cubic phase, and Co3 O4 cubic phase in pure and nanocomposites. The Williamson-Hall, Scherrer, and size-strain plot methods were employed to study the crystalline development and contribution of micro-strain. FTIR pattern exhibited the metal-oxygen and PANI bond vibrations. FE-SEM images shown the spherical core-shell shape morphology of quaternary nanocomposite. EDX evident the presence of praseodymium, cobalt, and nickel in synthesized samples. UV–vis spectroscopy confirmed the absorption in the visible region. The IV graphs showed a higher conductivity of quaternary nanocomposite. The cyclic voltammetry results revealed that the quaternary nanocomposite has a higher specific capacitance 500 Fg -1 as compared to binary nanocomposites 134 F g −1 (PANI-Pr2 O3 ), 143 F g −1 (PANI-Co3 O4 ), 256 F g −1 (PANI-NiO), and PANI (90.8 F g −1 ) at a scan rate of 5 m Vs −1 . The GCD results also showed that the quaternary nanocomposite has a higher specific capacitance of 905 F g −1 at current density 1 A g −1 with maximum energy density and power density of 87.99 kWhkg -1 and 2.6 k W kg −1, respectively. The EIS curve also confirmed that the quaternary nanocomposite has a lower polarization resistance (Rp ) and solution resistance (Rs ). The higher capacitance of quaternary nanocomposite can facilitate ion transfer, and the formation of its core-shell structure flourish to enhance surface-dependent electrochemical properties. Furthermore, this study gives a novel research idea to manufacture electrode materials for supercapacitors.